2016
DOI: 10.3390/min6030095
|View full text |Cite
|
Sign up to set email alerts
|

China’s Rare Earths Supply Forecast in 2025: A Dynamic Computable General Equilibrium Analysis

Abstract: The supply of rare earths in China has been the focus of significant attention in recent years. Due to changes in regulatory policies and the development of strategic emerging industries, it is critical to investigate the scenario of rare earth supplies in 2025. To address this question, this paper constructed a dynamic computable equilibrium (DCGE) model to forecast the production, domestic supply, and export of China's rare earths in 2025. Based on our analysis, production will increase by 10.8%-12.6% and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The export license on REs was enforced in 2015, which drove the study of China's supply trends to become a hot topic of the world. Various researchers have shown interest in the production forecast of China, among which Jianping Ge and Yalin Lei [6,[40][41][42][43] have made significant contributions.…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The export license on REs was enforced in 2015, which drove the study of China's supply trends to become a hot topic of the world. Various researchers have shown interest in the production forecast of China, among which Jianping Ge and Yalin Lei [6,[40][41][42][43] have made significant contributions.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Furthermore, in consideration of changes in regulatory policies and the development of strategic emerging industries, it was critical to investigate the scene of RE supplies. Ge and Lei [41] forecasted the production, domestic supply, and export of China's REs in 2025 by constructing a dynamic computable equilibrium (DCGE) model. From a policy perspective, they found that the elimination of export regulations, including export quotas and export taxes, did have a negative impact on China's future domestic supply of REs.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…(2017b ) construct a computable general equilibrium (CGE) model to investigate the market impacts of environmental regulation on the production of rare earths in China. Likewise, Ge et al. (2016 ) constructed a dynamic computable general equilibrium (DCGE) model to forecast the production, domestic supply, and export of China's rare earths in 2025.…”
Section: Introductionmentioning
confidence: 99%
“…A review of global REE abundance and current mining and recovery methods, underlining environmental costs, is presented in [ 22 ], while evaluation of global REE demand is considered in [ 23 ]. China’s dynamic computable equilibrium supply model forecast up to 2025 was also described [ 24 ], together with its sustainable development policies [ 25 ]. Reduction of environmental burdens and a European production chain was also proposed [ 26 ].…”
Section: Introductionmentioning
confidence: 99%